Relationship between Breech Delivery and The Condition of Mother and Baby at RSIA Permata Hati - Fathiyati, Fathiyati; Al-Bahra, Al-Bahra (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
The aim of this research is to determine the relationship between breech delivery and the condition of the mother and baby at RSIA Permata Hati in 2021. The conceptual framework in this research is the independent variables in the form of maternal age, parity, history of previous births, gestational age, hydramnios, placenta previa and pregnancy. twins and the dependent variable is breech position. It is hoped that the benefits of this research can be used as a source of reference in handling breech delivery. In this study the author used a descriptive method by collecting data using secondary data from (Medical Records). Data analysis was carried out univariately and bivariately with a population distribution of the frequency of breech position events that occurred at RSIA Permata Hati in 2021 as many as 133 people. The results of the overall study showed that 68 people (68%) experienced pure buttock breech births and those who experienced 32 people (32%) conveyed the location of the breech buttocks. The maternal age at risk of breech delivery was 41 people (41%) and the age without risk was 59 people (59%). And 59 mothers (59%) had a previous delivery history and 41 mothers (41%) did not have a previous delivery history. With the results of the research above, it is hoped that health workers can improve the quality of services, especially in handling breech cases and can improve the quality of existing services again.